Effectiveness of a structured weight management programme at workplace among employees of a petroleum industry in Malaysia - Roszanadia Rusali; Suzana Shahar; Lee, Xiao Wen; Zahara Abdul Manaf (Penerbit Universiti Kebangsaan Malaysia, 2016)
Recognising the epidemic of overweight and obesity among Malaysians, formulation of intervention programmes such as a weight management programme at workplace is essential. This study aimed to determine the effectiveness of a structured weight management programme at workplace among overweight and obese employees. In this quasi-experimental study, sixty-four of overweight and obese adults were recruited and divided into two groups (intervention group, n = 32 and control group, n = 32). Subjects in the intervention group received three months scheduled programme and the control group received a routine weight management consultation from dietitians. Significant group effect was found on waist circumference (WC) in men (p < 0.05) and Body Mass Index (BMI) in women (p < 0.05). Men from the intervention group had reduced their WC by 3.4% (-3.7 cm) as compared to controls of 0.7% (-0.8 cm). Women in the intervention group improved their BMI by 1.4% (-0.4 kg/m2) as compared to controls at 0.3% (-0.1 kg/m2). Total cholesterol and LDL-C reduced among women in both intervention and control group with significant time effect (p < 0.05). As a conclusion a structured weight management programme effectively improved WC in men and BMI in women, and appeared to be as effective as individual diet counselling by dietitians in improving lipid profiles in women.